GASTON BACHELARD AND JOSÉ AMÉRICO: A PLAYFUL GAME OF PHILOSOPHIZING - Bulcão, Marly (Revista Inter-Legere, 2018)
The purpose of this work is to make a rapprochement between José Américo Pessanha, a Brazilian thinker who taught through his lectures a personal philosophy, and Gaston Bachelard, a French philosopher of undeniable importance. Both of them, starting from a critique of tradition, renew the notions of reason and imagination. The development of this work will make it evident that, for both of them, it does not make sense at the present time to accept the idea of ??a single, universal and timeless reason. They exalt, therefore, the character of historicity of reason which, in the course of its progress, is renewed, rectified, re-established, as well as establishes new truths. On the other hand, on the contrary to what the tradition wanted, the imagination can not be understood as a simulacrum of the perceived real, as this would lead to the overlook of it before the perception and the idea. The conclusion will finally show that the proposal of a new notion of reason and imagination will have repercussions on the conception of culture, revealing the importance of the reflections of Bachelard and José Américo for contemporaneity. Keywords: Bachelard. José Américo. Reason. Imagination.